Diastolic dysfunction of ventricles in patients with calcium pyrophosphate crystal deposition disease while receiving anti-inflammatory therapy - Maxim S. Eliseev; Olga V. Zheliabina; Irina G. Kirillova; Yulia O. Korsakova (Терапевтический архив, 2023)
Background. Calcium pyrophosphate crystal deposition disease (CPPD) may be associated with developing of diastolic dysfunction (DD).